Faktor-Faktor yang Mempengaruhi Keberhasilan UKM di Kabupaten Sleman berdasarkan Formal Concept Analysis - Muslim, Rudi; Pratama, Ahmad Raf’ie; Hidayat, Taufiq (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2020)
Small Medium Enterprises (SME) play an important role in the economic growth of Indonesia, and it was no exception in Sleman Regency, D.I. Yogyakarta province. This study aims to investigate and to recommend factors driving SME success by using formal concept analysis (FCA). Eleven factors and 36 subfactors were found based on the literature study to be further tested against a dataset based on interviews of 14 SMEs from seven different business sectors. With 95 attribute values from the attribute scaling process, the FCA results showed 641 concepts and concept lattice visualizations. Using a support threshold of 64%, seven intents were found to be more important, while other intents not included in the iceberg concept lattices were considered to be less important. The findings show that five factors (i.e., customers, products, human resources, networks, and external influences) play more important roles in driving SME success in Sleman Regency than the other six factors (i.e., characteristics, finance, competitors, market, technology, and government policy).